The relationship between microRNAs and the STAT3-related signaling pathway in cancer - Lin Zhang; Junyao Li; Qi Wang; Guangping Meng; Xuejiao Lv; Hong Zhou; Wei Li; Jie Zhang (Tumor Biology)
MicroRNAs are non-coding RNAs that regulate gene expression by targeting messenger RNA molecules in 3′ untranslated region. Mounting evidence indicates that microRNAs regulate several factors to influence various biological activities that are related to carcinogenesis, including signal transducer and activator of transcription 3, which is a transcription factor that also acts as an oncogene. MicroRNAs influence signal transducer and activator of transcription 3 either by directly targeting or via other pathway components upstream or downstream of signal transducer and activator of transcription 3 such as Janus kinases, members of the suppressor of cytokine signaling family, and other genes that regulate cell proliferation, apoptosis, migration, invasion, and epithelial–mesenchymal transition. However, signal transducer and activator of transcription 3 activation changes the pattern of expression of microRNAs and mediates tumorigenesis. Moreover, the relationship between signal transducer and activator of transcription 3 and microRNAs varies among different kinds of cancers. A specific microRNA may act as an oncogene or tumor suppressor in different cancers, and microRNAs also directly or indirectly regulate signal transducer and activator of transcription 3 via pathways in the same cancers. In this review, we focus on the reciprocal regulation and roles of microRNAs and signal transducer and activator of transcription 3 in cancer, as well as describe current research progress on this relationship. A better understanding of this relationship may facilitate in the identification of targets for clinical therapeutics.